Can the use of femoral notch view alone decrease measurement error of distal interlocking screws after retrograde femoral nailing. Issue 4 (April 2019) - Liu, Boshen; Zuelzer, David A.; Allen, Jerad; Comadoll, Shea; Hsu, Joseph R.; Swart, Eric F.; Matuszewski, Paul E.
Highlights: Differentiating distal interlocking screw lengths on traditional imaging (AP/Notch/Tangential) is poor. The addition of the femoral notch view with the traditional PA view can maximize a surgeon's ability to detect prominent distal interlocking screws. Careful intraoperative radiographic assessment with multiple views could decrease the need for symptomatic screw removal. Abstract: Objectives: Determine if using different fluoroscopic views of the knee (Notch or Tangential) improves accuracy of screw lengths assessment compared to the standard posteroanterior (PA). Participants and Methods: Orthopaedic surgeons at three ACGME-accredited residency programs were asked via survey to assess screw lengths on PA, femoral notch, and tangential radiographic views. Results: Responders correctly identified screw length using PA, femoral notch, and medial tangential views at rates of 46.75%, 52.27%, and 44.37% respectively. Respondents detected overall screw length discrepancies most accurately using the femoral notch view (Odds Ratio 1.26; 95% confidence interval: 1.07–1.47; P < 0.005). There was no statistical difference between the residents and faculty cohort in ability to detect screw length discrepancy. Conclusion: Differentiating distal interlocking screw lengths on traditional imaging (AP/Notch/Tangential) is poor. The femoral notch view significantly improves accuracy in radiographic determination of screw length. The femoral notch view should be used in conjunction with the traditional PA view to maximize sensitivity and specificity for detecting prominent screws.